Research advances and future perspectives of genomics and genetic improvement in allotetraploid common carp - Lin Chen; Jian Xu; Xiaowen Sun; Peng Xu (Reviews in Aquaculture, 2022)
Aquatic species have become an integral part of human culture. As an internationally important food fish species, the common carp Cyprinus carpio accounted for over 7% of global aquaculture production in 2020. In addition to serving as a food source, common carp varieties are used as ornamental fish and valued in recreational fisheries. The continuously updated reference genome of common carp has recently served as a foundation for both basic genetic studies and evolutionary studies. With the recent emphasis on the allotetraploid signature of common carp, researchers have begun to focus on how hybridization and polyploidization affect the successful speciation and advantageous behaviour of common carp. In this review, we survey current and emerging research topics on common carp, including genomic and genetic tools, germplasm resources, genetic diversity, genetic mechanism and improvement of economic traits, as well as multiple breeding technologies employed in common carp. We also provide an overview of recent trends in genetic studies and improvements in common carp and encourage researchers to monitor the allotetraploid signature of common carp. Understanding the genetic basis of economically important traits and the mechanisms of allopolyploidization in common carp will be important for genetic improvement and germplasm innovation in agronomically important fish species, although the road ahead will be challenging for this widely domesticated allotetraploid species.